Efektivitas Media Pembelajaran Komik Keperawatan Interaktif Imun-Toon terhadap Keterampilan Kognitif Mahasiswa Keperawatan - Kristina; Ismiati, Theresia Tutik (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
Background: Sufficient knowledge of nursing care is the main requirement in caring for patients, it takesinteresting and interactive learning materials so that nursing students can learn well and understand thenursing care that will be provided.Purpose: This study aims to provide a selection of interesting learning materials in the form of interactivecomics about nursing care in patients with cancer.Research method: this study used true experimental design with post test-only control design. There were80 respondents to the fifth semester nursing students, the treatment group as many as 40 respondents andthe control group as many as 40 respondents. The sampling technique used was purposive sampling byselecting samples according to the inclusion criteria. The treatment group received learning materials inthe form of nursing comics and the control group was given handouts. After getting teaching about nursingcare to cancer patients for 2 meetings, a written evaluation was carried out with a cognitive level questioncategory 1 - 3. Student scores were processed using the SPSS 24 program with independent t-test analysis.Results: the results of the analysis showed that after using nursing comic learning materials in thetreatment group and handouts in the control group, there was a significant difference in value 000 <0.05,where the learning outcomes in the treatment group showed an average result of 72.6 and an average valueof 60.4 in control group.Conclusion: nursing interactive comic learning media is effective in improving nursing student learningoutcomes.